Impact of initial screening strategies on compliance with colonoscopy for colorectal carcinoma in residents aged 50 years and above - XIANG Fang; HU Zhihao; WANG Yawei; ZHANG Yiying; HUANG Fang; PENG Qian; YU Hongjie; FU Chaowei (Shanghai yufang yixue)
ObjectiveTo compare colonoscopy compliance rates under different screening strategies, to explore ways to enhance colonoscopy compliance among residents with colorectal carcinoma.MethodsResidents aged between 50‒80 years were recruited through extensive community outreach and voluntary participation. A total of 210 630 residents who participated in the colorectal carcinoma screening program in Jiading District, Shanghai, between 2013 and 2019 were selected as the research subjects. All subjects underwent a colorectal carcinoma risk assessment questionnaire survey and two fecal occult blood tests (FOBT). Positive results in the initial screening were defined as a positive questionnaire survey or a positive result in at least one FOBT. Participants with positive initial screening results were advised to undergo colonoscopy screening in a hospital. Colonoscopy results were collected from hospital reports and physician follow-ups. Compliance with colonoscopy was analyzed under different screening strategies to identify possible factors influencing residents’ willingness to undergo the procedure.ResultsA total of 21 403 individuals (10.16%) were identified as positive with the questionnaire survey, 31 595 individuals (15.00%) tested positive with at least one FOBT. Combined questionnaire and FOBT positivity was observed in 3 501 individuals (1.66%). Among the 48 453 individuals with positive initial screening results, 17 230 (35.56%) underwent colonoscopy, and a total of 315 cases of colorectal cancer were detected. The sensitivity, specificity value of FOBT initial screening were 83.81% and 84.66%, respectively. According to the combined risk assessment and FOBT initial screening preliminary screening, the lowest colonoscopy compliance rate (25.63%) was observed among individuals with only a positive questionnaire, and the highest compliance rate (52.55%) was among those with both positive questionnaire survey and two positive FOBT results. Multivariate analysis revealed that FOBT positivity had the greatest impact on colonoscopy compliance. Those with one positive FOBT test result were 2.64 times more likely to undergo colonoscopy screening than those with negative FOBT results, while individuals with two positive FOBT results were 3.18 times more likely to do so. After adjusting for FOBT results, individuals with positive questionnaire survey results were 1.43 times more likely to undergo colonoscopy screening than those with negative results (95%CI: 1.34‒1.52). Compared to questionnaire-based risk assessment, FOBT results were more influential in determining compliance with colonoscopy.ConclusionThe choice of initial screening method significantly impacts residents’ compliance with colonoscopy. While implementing colorectal carcinoma screening programs, it is necessary to strictly adhere to screening protocols, including risk assessment and FOBT. Additionally, efforts should be made to raise public awareness, encouraging residents to actively participate in risk assessments and FOBT, thereby improving their compliance with colonoscopy.